kebungkaman celie atas kekerasan seksual dalam novel the color purple oleh alice walker - neisya neisya (Jurnal Lingua Idea, 2017)
The issue of sexual violence is not becoming a strange thing in the public nowadays. Many victims of such violence still chose to keep silent by not voicing their suffering. This study tried to capture this fonomena through a novel character, Celie, in Alice Walker's The Color Purple. Celie's silence on sexual harassment and physical violence on her due to the chaos of mental development where the id, ego and superego phases do not run properly. Fear of her stepfather's threats were a strong reason for her silence. The purpose of this study was to reveal the mental development of a sexual violence victim from the perspective of Freud's psychoanalysis. The methods used are literature studies where researchers attempt to associate the story in the novel related to the sexual harassment issue with Freud's theory.